Reverse Logistics Practices and Organizational Performance. The Moderating Role of Organizational Learning Capabilities - Issah, Ofori; Agboyi, Makafui R.; Hanson, Obiri Yeboah; Adarkwa, Alvin Kweku (International Journal of Supply Chain and Logistics, 2024)
Purpose: The study assessed the influence of reverse logistics on organizational performance. The study also assessed the moderating effect of organizational learning capabilities on the relationship between reverse logistics and organizational performance Methodology: The research design for this study was a single cross-sectional survey where a quantitative approach was adopted. Convenience sampling was utilized to select participants 215 for the study due to its practicality and accessibility. Findings: Findings of the study concluded that reverse logistics has a positive and significant influence on organizational performance. Findings of the study also concluded that organizational learning capabilities positively and significantly moderate the relationship between reverse logistics and organizational performance. Unique Contribution to Theory, Policy and Practice: The study recommends that organizations foster an organizational culture where employees are encouraged to ask questions, seek out new knowledge, and experiment with new ideas; implement recognition and reward systems that celebrate learning and innovation; and develop centralized repositories where employees can store and access organizational knowledge, including best practices, project learnings, and research findings.